Aula dialogada na educação médica : um estudo quantitativo - Cunha, Laura Severo da (2015)
Study the medical education process is part of a worldwide movement of health review, motivating important initiatives, represented in Brazil by the national curriculum guidelines of the courses in this area, presented by the Ministry of Education in 2001. In order to compare the effects of content learning/retention (outcome) of dialogued lecture (factor under study), we carried out a randomized controlled trial by groups, blinded to the research subjects with medical students from the 7th and 8 th semester from a private university in southern Brazil, with grade five assigned by the Higher Education Personal Improvement Commission (CAPES). 150 subjects were evaluated between March 2012 and June 2014, average age 24.7 years and a predominance of females (62.7%); 69 (46%) allocated for dialogued lecture (intervention group) and 81 (54%) to traditional lecture (control group). The performance of groups was evaluated by the same theoretical knowledge test administered before and after class, where students in the control group showed greater variation between the first and second test (8.6 vs. 6.7 p = 0.0001) result reinforced by the magnitude of the effect also higher in this group (2,526 vs. 1,350). In the pretest, without distinction by group, the overall student achievement was 50%, with a higher average score of the intervention group (p = 0.003) and those students tested in the 7th semester. In this study, the expository dialogue-class determined final results similar to traditional classroom (20.2 vs. 20.0 points in the final test) no impairment in short-term learning was noticed.